2022
DOI: 10.1021/acs.jafc.1c05822
|View full text |Cite
|
Sign up to set email alerts
|

Bee Products: An Emblematic Example of Underutilized Sources of Bioactive Compounds

Abstract: Beside honey, honeybees (Apis mellifera L.) are able to produce many byproducts, including bee pollen, propolis, bee bread, royal jelly, and beeswax. Even if the medicinal properties of these byproducts have been recognized for thousands of years by the ancient civilizations, in the modern era, they have a limited use, essentially as nutritional supplements or health products. However, these natural products are excellent sources of bioactive compounds, macro-and micronutrients, that, in a synergistic way, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 133 publications
0
38
0
1
Order By: Relevance
“…Plant extracts are rich in many important non-nutritional and biologically active compounds such as phytochemicals. Among these different phytochemicals, it was found that total phenolic (TPC) and total flavonoid compounds (TFC) have attracted attention in the last few years in various food products [ 24 , 25 , 26 ]. Many studies have demonstrated a positive relationship between TPC and antioxidant activity in several fruits and plants [ 5 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts are rich in many important non-nutritional and biologically active compounds such as phytochemicals. Among these different phytochemicals, it was found that total phenolic (TPC) and total flavonoid compounds (TFC) have attracted attention in the last few years in various food products [ 24 , 25 , 26 ]. Many studies have demonstrated a positive relationship between TPC and antioxidant activity in several fruits and plants [ 5 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bee products such as bee pollen (BP), propolis, bee bread (BB), royal jelly (RJ) and beeswax (BW) can all function as active pharmaceutical ingredients. Royal jelly is marketed on a large scale in Asia, especially in China and Japan, as a health food and cosmetic product [ 3 , 4 ]. As a bee product, royal jelly (RJ) is used to maintain human health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have repeatedly pointed to the longevity-promoting properties of different honeybee products such as royal jelly, bee pollen, propolis, and honey [ 189 , 190 , 191 ]. In the frame of reviewing the use of bee products in dermatology, royal jelly has a multitude of pharmacological effects such as anti-inflammatory, antiallergenic, antibiotic, and antiaging.…”
Section: Honeybee Productsmentioning
confidence: 99%